Verification of Social and Economic Determination of Crime in Ukraine - LAVRUK, Vitalii V.; ZAPOROZHETS, Hanna V.; KHOMUTENKO, Oleksii V.; DUDCHENKO, Alexander Yu.; DEMIDOVA, Evgeniya E. (Journal of Advanced Research in Law and Economics; Vol 9 No 7 (2018): JARLE Volume IX Issue 7(37) Winter 2018DO - 10.14505//jarle.v9.7(37).20, 2019)
The article is devoted to the study of the features of socio-economic determination of crime in Ukraine for the entire period of its independence, since 1991. A comparative analysis of the trends in the main macroeconomic indicators of the determinants and the level of crime in Ukraine for the period 2000 – 2017, when changes in the level of crime in the country began to reflect the course and results of the reform, and not the laws of the transition economy. Comparison of the results of the empirical study with the theoretical positions of science made it possible to establish the truth of the theory of depression-expansion, which provides that crime grows during periods of economic ups and downs, and economic stability acts on crime in a mitigating way. A direct correlation between the level of crime and the level of unemployment has been traced. Indicators of socio-economic security in Ukraine for the period 2013 – 2017 are determined. Priority directions of modernization of social and economic policy of the state on prevention of growth of criminality are allocated.